The analysis of IT school examination material of 2002 year - Kaklauskas, Liudas; Narkienė, Vilma (Lietuvos matematikos rinkinys, 2003)
In the article analyzing IT examination material of 2002 year. For this purposes providing inquest teachers of informatics and results are evaluates by using statistical methods. Results of observing show, that 43% tasks of examine conform a program and 59% themes of examine program conform ECDL scale of estimation computer skills. Variants of examine tasks are equivalent (r meaning from 0.6 to 0.84, r2 meaning from 0.36 to 0.71). Analysis content for examinematerial feel the absence of verifying a wide theoretical and practical skills.